Variation in shoaling behavior in lake Mývatn threespine stickleback in relation to temperature and origin - Spencer William Edwards 1999- (2023)
Behavioral variation within populations has the potential to facilitate local adaptation and population divergence. The threespine stickleback (Gasterosteus aculeatus) in Lake Mývatn is an ideal candidate to study such local adaptations. Threespine stickleback diverge in their morphology and physiology across the lake, partly in relation to habitat diversity, e.g. in temperature. However, investigating behavioral differences within the population has been lacking. In the present study, I investigated whether variation in parental habitat of origin, which vary widely in temperature, predator densities, and geological features have an impact on the shoaling behavior of juvenile stickleback of lake Mývatn. Fish were reared at contrasting temperatures (22 °C and 13°C) for 5-7 months. Shoaling was tested by placing a single fish in an arena with a shoal and two distractors and behaviour recorded for 15 minutes, where time spent near the shoal was examined. I studied if the tendency to shoal was related to habitat of origin and rearing conditions, as well as whether it was related to fish size. I found that all fish show a strong tendency to shoal, but that time spent shoaling (versus interacting with distractors/exploring) is greater among fish raised in the cold treatment, regardless of parental origin. I found no correlation between size and shoaling time. My research will help us to better understand patterns of diversification across lake Mývatn and could be further replicated for other ecologically significant populations. Furthermore, understanding how behavior, morphology, and environment interact may increase our ability to predict how populations will respond to environmental change. Breytileiki í atferli innan stofna getur ýtt undir staðbundnar aðlaganir og þróunaraðskilnað. Hornsíli (Gasterosteus aculeatus) í Mývatni eru tilvalin til að rannsaka slíkar aðlaganir. Hornsílin í vatninu hafa sýnt breytileika í útliti og lífeðlisfræðilegum þáttum og tengist sá breytileiki fjölbreytileika búsvæða, t.d. í ...